2002
DOI: 10.1523/jneurosci.22-24-10731.2002
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Receptors Mediate Changes in Spinal Motoneuron Development and Axonal Pathfinding in Embryonic Zebrafish Exposed to Nicotine

Abstract: We show that transient exposure of embryonic zebrafish to nicotine delays the development of secondary spinal motoneurons. Furthermore, there is a long-lasting alteration in axonal pathfinding in secondary motoneurons that is not ameliorated by drug withdrawal. These effects of nicotine were reversed by mammalian nicotinic receptor antagonists. Coupled with these changes is a long-term alteration in swimming behavior. Our results show that transient embryonic exposure to nicotine leads to long-lasting effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 42 publications
7
78
1
Order By: Relevance
“…Dlugos and Rabin (Dlugos and Rabin, 2003) and Gerlai et al (Gerlai et al, 2006) have also demonstrated adaptation of adult zebrafish after chronic exposure to ethanol such that tolerance to the acute effects of the drug develops. By contrast, studies of the effect of nicotine on zebrafish development and behaviour are limited (Levin et al, 2007;Levin and Chen, 2004;Levin et al, 2006;Matta et al, 2007;Svoboda et al, 2002). Levin et al have shown that 3·min exposure to low doses of nicotine (38-77·mol·l -1 nicotine) improves memory function in zebrafish (Levin and Chen, 2004) and that acute exposure to similar concentrations has an anxiolytic effect (Levin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Dlugos and Rabin (Dlugos and Rabin, 2003) and Gerlai et al (Gerlai et al, 2006) have also demonstrated adaptation of adult zebrafish after chronic exposure to ethanol such that tolerance to the acute effects of the drug develops. By contrast, studies of the effect of nicotine on zebrafish development and behaviour are limited (Levin et al, 2007;Levin and Chen, 2004;Levin et al, 2006;Matta et al, 2007;Svoboda et al, 2002). Levin et al have shown that 3·min exposure to low doses of nicotine (38-77·mol·l -1 nicotine) improves memory function in zebrafish (Levin and Chen, 2004) and that acute exposure to similar concentrations has an anxiolytic effect (Levin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Levin and Chen (2004) and Levin et al (2006b) have studied extensively the effects of nicotine on learning and memory in zebrafish and have shown that low doses of nicotine enhance memory while higher doses impair memory in zebrafish. Zebrafish larvae possess acetylcholinesterase with similar enzymatic activity to other vertebrates, but do not have butyrylcholinesterase (Svoboda et al, 2002), and cloning and binding experiments have demonstrated the presence of nicotinic (b3, a2, and a7 subunits) (Zirger et al, 2003) and muscarinic receptors (Williams and Messer, 2004) in zebrafish embryo. To determine whether the enhanced startle response observed with the cholinesterase inhibitor donepezil was mediated via either nicotinic or muscarinic receptors or both types of receptors, donepezil treatment was combined with the nicotinic antagonist mecamylamine or the muscarinic antagonist atropine.…”
Section: Discussionmentioning
confidence: 99%
“…A pioneering study of nicotine effects on neural development demonstrated that exposure early in embryonic development induced axons path-finding errors (Svoboda, Vijayaraghavan, & Tanguay, 2002). Zebrafish were exposed to 5, 15, and 33 mM nicotine, with 33 mM selected for most experiments because it elicited the strongest alteration in embryonic zebrafish behavior.…”
Section: Embryonic Developmentmentioning
confidence: 99%